Update: Immunotherapeutic Strategies in HPV-Associated Head and Neck Squamous Cell Carcinoma - Fangdi Sun; A. Dimitrios Colevas (Viruses)
The incidence of human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (OPSCC) has increased substantially over the past three decades, and since 2017, it has been recognized in the AJCC staging system as distinct from its HPV-negative counterpart. The underlying mechanisms of HPV-associated carcinogenesis, tumor microenvironment, and host immune response represent opportunities for therapeutic development. While anti-PD-1 immunotherapy is now part of standard treatment for recurrent or metastatic head and neck squamous cell carcinoma (HNSCC) in general, there are no established immunotherapeutic strategies specifically for HPV-related HNSCC. In this context, multiple emerging approaches are being actively studied—among these are therapeutic vaccines with or without anti-PD-(L)1 adjuvants, peptide–HLA-based immunotherapeutic platforms, and adoptive cell therapies including tumor-infiltrating lymphocytes (TILs), T-cell receptor (TCR) therapy, and chimeric antigen receptor (CAR) T-cell therapy. Beyond further maturation of these novel immunotherapeutic strategies, additional work is needed to delineate the optimal disease state of application (localized versus recurrent/metastatic), as well as in the development of small molecule inhibitors targeting HPV-specific mechanisms of viral oncogenesis.